Knowledge Transfer Strategies in Non-Formal Education: Improving Digital Literacy Among Rural Youth Through Community Outreach Programs - Agus; Billiah G; Nakijoba (Zabags International Journal of Engagement, 2026)
The study addresses the persistent digital divide experienced by rural youth, particularly in relation to limited access to technology, inadequate internet infrastructure, and low levels of digital literacy. The primary objective is to analyze the implementation of knowledge transfer strategies within non-formal education programs based on community outreach and to assess their contribution to enhancing digital literacy among rural youth. Employing a descriptive qualitative approach with a case study strategy, data were collected through in-depth interviews, participatory observation, focus group discussions, and program documentation. Findings reveal that knowledge transfer strategies such as mentoring, group discussions, and digital practice simulations effectively improved participants’ abilities to access, evaluate, and create digital content, while also strengthening their engagement in community-based activities. Supporting factors included local community involvement and active facilitator participation, whereas challenges stemmed from limited infrastructure and digital devices. The study contributes theoretically by reinforcing the relevance of Knowledge Transfer Theory, Experiential Learning Theory, Digital Literacy Framework, and Community-Based Learning Theory in the context of non-formal education. Practically, it demonstrates the potential of community-based strategies to bridge the digital divide in rural areas. The implications highlight the need for adaptive digital literacy programs tailored to local contexts and provide strategic recommendations for practitioners and policymakers to foster sustainable digital inclusion among rural youth.